Kepemimpinan Kepala Madrasah Dalam Upaya Meningkatkan Kinerja Guru di SD Islam Integral Luqman Al Hakim 02 Batam - Siti Nur Mawaddah (STIKes Ibnu Sina Ajibarang, 2024)
This research is specifically to find out how the principal's leadership in improving teacher performance at SD Islam Integral Luqman Al Hakim 02 Batam, the factors that can influence and factors that can improve teacher performance, are expected. By knowing all that, some suggestions can be given that can be taken into consideration for school principals, especially in improving the performance of teachers in their schools. The essence of the principal's leadership is aimed at guiding and fostering teachers to become professional teachers and have achievements and performance and teaching skills. The teacher is the most decisive component in the education system as a whole, which must receive central attention. This figure will always be a strategic spotlight when talking about education issues, because teachers are always associated with any component in the education system, especially in relation to the teaching and learning process. With a professional teacher, a further goal, namely improving student learning outcomes will be achieved. It is the principal's duty as a leader to assist teachers in improving teacher professionalism and performance. While there are still many teachers who in carrying out learning activities have not met expectations. Therefore, the author needs to examine the pattern of Principal Leadership in an effort to improve teacher performance at SD Islam Integral Luqman Al Hakim 02 Batam. From the results of the study it was stated that the principal's leadership was considered good, but had not had a positive impact on improving teacher performance at SD Islam Integral Luqman Al Hakim 02 Batam While the performance of teachers at SD Islam Integral Luqman Al Hakim 02 Batam is considered good, but has not run optimally as expected, this is due to the lack of teacher ability in preparing learning tools, especially Learning Implementation Plans, inadequate school facilities and infrastructure, and also the difficulties of teachers in creating educational interactions between students and teachers, as well as the difficulty of creating a conducive classroom. However, at the level of evaluation/assessment of learning outcomes, the average teacher has implemented it well and added remedial and enrichment programs